Life changing response to successive surgical interventions on cranial venous outflow: A case report on chronic fatigue syndrome - Higgins, J. Nicholas P.; Axon, Patrick R.; Lever, Andrew M. L. (Frontiers in Neurology, 2023)
Recognition of similarities between chronic fatigue syndrome and idiopathic intracranial hypertension (IIH) has raised suggestions that they might be connected, with chronic fatigue syndrome representing a mild version of IIH, sharing many of its symptoms, but without the signature features of raised intracranial pressure that characterise the syndrome in full. A further development of this idea factors in the effects of a cerebrospinal fluid leak, a known complication of IIH, to explain cases where symptoms seem out of proportion to the apparent physiological disturbance. Cranial venous outflow obstruction has been postulated as the fundamental pathological substrate. We describe a patient with multiple symptoms, including headache and disabling fatigue, in which this model guided investigation and treatment. Specifically, CT and catheter venography identified focal narrowings of both jugular and the left brachiocephalic veins. Treatment of brachiocephalic obstruction was not feasible. However, in separate surgical procedures, relief of jugular venous obstruction produced incremental and significant clinical improvements which have proved durable over the length of follow up. We suggest that investigating chronic fatigue syndrome under this model might not only bring benefit to individual patients but will provide new insights into IIH and its relationship with spontaneous intracranial hypotension.